Pengaruh Motivasi Belajar Santri Terhadap Peningkatan Kajian Kitab Salaf Pesantren Darussalam Blokagung Tegalsari Banyuwangi Tahun 2016 - M. Khozin Kharis (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2017)
This research aims to: (1) Knowing the learning motivation of students in improving the study of the book of the salaf in pesantren Darussalam Blokagung Tegalsari Banyuwangi, (2) Determine the study of the book of the salaf in pesantren Darussalam Blokagung Tegalsari Banyuwangi, (3) Determine the influence of learning motivation of students to increase study the book of the salaf in pesantren Darussalam Blokagung Tegalsari Banyuwangi. This research uses descriptive quantitative method with engineering product moment pada test the validity of data and to search for data reliability using the formula alpha, whereas the hypothesis test using F test and T, then to test data normality test was used non-parametric tests and data analysis using regression model, Popoulasi this study were boarding school students Darussalam, amounting to 100. After analyzing the data collected, it was found that (1) learning motivation of students is very good. (2) The increase in the book of the Salaf study is very good. (3) There is an effect of learning motivation of students to study the book of the Salaf increase.